Inhibition of Myocardial Ischemia/Reperfusion Injury by Exosomes Secreted from Mesenchymal Stem Cells - Heng Zhang; Meng Xiang; Dan Meng; Ning Sun; Sifeng Chen (Stem Cells International)
Exosomes secreted by mesenchymal stem cells have shown great therapeutic potential in regenerative medicine. In this study, we performed meta-analysis to assess the clinical effectiveness of using exosomes in ischemia/reperfusion injury based on the reports published between January 2000 and September 2015 and indexed in the PUBMED and Web of Science databases. The effect of exosomes on heart function was evaluated according to the following parameters: the area at risk as a percentage of the left ventricle, infarct size as a percentage of the area at risk, infarct size as a percentage of the left ventricle, left ventricular ejection fraction, left ventricular fraction shortening, end-diastolic volume, and end-systolic volume. Our analysis indicated that the currently available evidence confirmed the therapeutic potential of mesenchymal stem cell-secreted exosomes in the improvement of heart function. However, further mechanistic studies, therapeutic safety, and clinical trials are required for optimization and validation of this approach to cardiac regeneration after ischemia/reperfusion injury.